Optimization of Gelatin Fibrous Scaffold Properties by PCL and CMC by Using Electrospinning Technique - Banpot Meesa; Sakon Klongboonjit (My University, 2025)
This study aimed to utilize the electrospinning process to produce cell culture scaffolds from blends of gelatin-polycaprolactone and carboxymethyl cellulose. The experimental design involved determining the optimal voltage and feed rate for various ratios of the gelatin-polycaprolactone-carboxymethyl cellulose blends, including 100/0/0, 90/5/5, 80/15/5, 70/25/5, and 60/35/5. Gelatin served as the primary raw material at a 10% ratio, while polycaprolactone was added at 10%, and carboxymethyl cellulose acted as a strengthening agent at 0.8%. The solvent used for gelatin and polycaprolactone was 2,2,2 -trifluoroethanol, while water was used for carboxymethyl cellulose. The raw materials were thoroughly mixed to ensure homogeneity, and the resulting blend was processed by an electrospinning machine under various conditions to form nanofiber scaffolds. The workpieces were then dried and left to relax for 48 hours before being baked at 140°C for 72 hours, resulting in high-quality fiber material. The experiment revealed that the fiber sizes ranged from 1.5 µm to 5.2 µm, with the swelling ratio of the GPC60:35:5 mixture at 11.65%, confirming the feasibility of using electrospinning to create effective scaffolds for cell culture applications.
Keywords: Electrospun Nanofibers in Biomedical Applications